1993
DOI: 10.1002/1097-0142(19930515)71:10<3119::aid-cncr2820711037>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant mitotane on the clinical course of patients with adrenocortical cancer

Abstract: Background. Adrenocortical carcinoma is a rare and aggressive disease with a poor prognosis. Adjuvant mitotane administration has been suggested as a strategy that might improve the outcome of patients with localized disease. Methods. The authors analyzed the clinical outcome of patients with localized or regional adrenocortical cancer. The study included 19 patients who were registered at M. D. Anderson Cancer Center during a 3‐year period and who had localized or regional disease at the time of surgery. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 16 publications
1
39
0
3
Order By: Relevance
“…The use of rather low doses of mitotane (up to 6 g daily) may explain why mitotane-related toxicity was acceptable (Kasperlik-Zaluska et al 1995, Dickstein et al 1998, while severe and disabling toxicity was reported in the studies where high, rapidly increasing, daily doses of mitotane were employed (Vassilopoulou-Sellin et al 1993, Schulick & Brennan 1999. In our series, all the patients experienced elevation of aPH and gGT and most patients reported also gastrointestinal Endocrine-Related Cancer (2008) 15 1043-1053 www.endocrinology-journals.org symptoms, but gastrointestinal and hepatic toxicities were of grade 1 in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rather low doses of mitotane (up to 6 g daily) may explain why mitotane-related toxicity was acceptable (Kasperlik-Zaluska et al 1995, Dickstein et al 1998, while severe and disabling toxicity was reported in the studies where high, rapidly increasing, daily doses of mitotane were employed (Vassilopoulou-Sellin et al 1993, Schulick & Brennan 1999. In our series, all the patients experienced elevation of aPH and gGT and most patients reported also gastrointestinal Endocrine-Related Cancer (2008) 15 1043-1053 www.endocrinology-journals.org symptoms, but gastrointestinal and hepatic toxicities were of grade 1 in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,20 In the current study, this complication was treated by the administration of daily hydrocortisone, and when indicated, supplemental fluorohydrocortisone. In the first few patients, replacement therapy was not initiated until there was clinical evidence of adrenal insufficiency or a high adrenocorticotropic hormone level was documented.…”
Section: Replacement Hormonal Therapymentioning
confidence: 91%
“…This concept coupled with a limited evidence of efficacy in the literature published since recently [5][6][7][8][13][14][15][16][17] made adjunctive treatment with mitotane progressively less appealing. As a matter of fact, no recommendation in favor or against adjuvant treatment was formulated at a consensus conference on ACC held at Ann Arbor in 2003 [18].…”
Section: Adjuvant Mitotane Treatment: What Is the Evidence?mentioning
confidence: 99%